“As it happens”: Co-creating knowledge for a gender-based safety audit with women experiencing long-term homelessness - Vaccaro, Mary-Elizabeth; Milliken, Stephanie; Samana, Yaungtinec; Floren, Samm (Canadian Social Work Review / Revue canadienne de service social, 2025)
In this paper, we explore an intersectional feminist approach to co-creating knowledge on safety with women and gender-diverse people experiencing long-term, street-based homelessness in Hamilton, Ontario. Using a gender-based safety audit (GBSA) framework, our project team of front-line social service providers, academic researchers, and community co-leads collaborated to engage participants in arts-based workshops to co-produce a zine focused on the community’s perceptions of safety and recommendations for action. Drawing from our own experiences as well as existing literature on the lived realities of women and gender-diverse people experiencing homelessness, our paper critically reflects on the barriers and ethical considerations inherent in knowledge co-creation projects with highly marginalized communities. By foregrounding the perspectives and recommendations of those directly affected by gender-based homelessness, our work also contributes to scholarship on feminist knowledge co-creation methodologies. Through reflexive dialogues within our project team, we highlight the transformative potential of arts-based knowledge co-creation projects that engage marginalized communities in advocating for social change.